2013
DOI: 10.1055/s-0033-1359319
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative cause of dementia and is responsible for significant individual morbidity and mortality, and economic impact on the health care system. Neurodegeneration (including neuronal atrophy and/or loss) are attributed to extraneuronal toxic amyloid oligomers and proteins, intraneuronal neurofibrillary tangles consisting of hyperphosphorylated tau, region-specific diminished cerebral glucose metabolism, synaptic dysfunction, and mitochondrial dysfunction. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
89
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 115 publications
1
89
1
8
Order By: Relevance
“…The biological coherence of the protein expression, compared to gene expression data, with respect to association with AD clinical features, was noteworthy, suggesting proteomic data may be a more informative measure for identifying important dysregulated pathways. Ab, a hallmark of AD (6), was consistently the protein with the highest expression in cases relative to controls, whereas VGF was the most downregulated. DE proteins are annotated for energy metabolism and immune and nervous system related processes, all previously implicated in AD (8,(94)(95)(96)(97)(98); our co-expression network analyses based in part on these DE protein studies, have further identified novel, potentially druggable targets within these pathways.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The biological coherence of the protein expression, compared to gene expression data, with respect to association with AD clinical features, was noteworthy, suggesting proteomic data may be a more informative measure for identifying important dysregulated pathways. Ab, a hallmark of AD (6), was consistently the protein with the highest expression in cases relative to controls, whereas VGF was the most downregulated. DE proteins are annotated for energy metabolism and immune and nervous system related processes, all previously implicated in AD (8,(94)(95)(96)(97)(98); our co-expression network analyses based in part on these DE protein studies, have further identified novel, potentially druggable targets within these pathways.…”
Section: Discussionmentioning
confidence: 95%
“…The brains of AD patients have hallmark senile plaques in the neuropil and around brain blood vessels, composed of accumulated amyloid beta (Ab), and neurofibrillary tangles (NFT) inside neurons, comprised of microtubule-associated hyperphosphorylated Tau protein (2). While therapeutic strategies to target Ab and tau pathologies have been aggressively pursued over the past two decades, the failure to date to deliver efficacious treatments from these efforts has increased the urgency to identify and pursue different mechanisms underlying AD, such as the immune system, through microglial cells, that has more recently been shown to play a key role in AD (3)(4)(5)(6)(7)(8)(9). Furthermore, with a handful of drugs lessening some of the symptoms of AD, no effective drugs are currently available that prevent, halt or reverse the onset or progression of this disease.…”
mentioning
confidence: 99%
“…In particular, among the possible triggers of the neurodegenerative process and in particular of AD, nutrients have the potential to be either prevention-or riskrelated factors. The study of their effects at the gene expression level, by means of nutrigenomic analyses, is a field of broad scientific interest [77,78]. Despite some conflicting evidences, plant-based, plant-rich diets and plant-derived bioactive nutrients appear to inhibit neuroinflammation and neurodegeneration molecular and cellular processes [79] and seem to be particularly beneficial in the management of early stages of cognitive impairment [80][81][82][83][84].…”
Section: The Population and Individual Levels: Epidemiological Studiementioning
confidence: 99%
“…Dementia is a global health burden . According to a recent report in 2015 from the World Health Organization, there are 47.5 million people living with dementia worldwide, and over 60% of dementia cases are caused by Alzheimer's disease (AD) .…”
mentioning
confidence: 99%
“…D ementia is a global health burden. 1,2 According to a recent report in 2015 from the World Health Organization, there are 47.5 million people living with dementia worldwide, and over 60% of dementia cases are caused by Alzheimer's disease (AD). 3 With a global aging population, the total number of people with AD or dementia is expected to significantly increase over the next 10 years.…”
mentioning
confidence: 99%